Community Contribution to the Increase of Tourists at the Dwarawati Temple Tourist Attraction - Frisca Dini Aurora Utari; Achmad Yusuf; Elgar Balasa Singkawijaya (International Journal of Geography, Social, and Multicultural Education, 2026)
Abstract The development of tourism can be observed through the number of tourists visiting a particular tourist destination. In recent times, tourism has become a focal point due to its potential to generate additional foreign exchange for the country. This study aims to examine public perception and the tourism appeal in relation to the low number of tourist visits to Dwarawati Temple, located in Wonosobo Regency, Central Java.The research method used is a qualitative approach. Data collection techniques include interviews, observation, and documentation. The data analysis technique employed in this study is triangulation, specifically source triangulation. The data collected is further strengthened with other supporting sources to enhance the validity of the findings.Based on the results of the study regarding the community's contribution to increasing tourist visits at the Dwarawati Temple tourist site, it can be concluded that active community participation has a significant impact on the development of the tourism sector. However, this contribution has not yet reached its optimal potential due to several major constraints. One of the most significant obstacles is the inadequate accessibility to the location of Dwarawati Temple, which makes it difficult for tourists to visit and directly affects the low number of visits. Keywords: Community Contribution, Tourist Increase, Dwarawati Temple